An Expedient Approach to Pyrazolo[3,4-b]pyridine-3-carboxamides via Palladium-Catalyzed Aminocarbonylation - Alam, Ryan M.; Keating, John J. (Synthesis, 2021)
Pyrazolo[3,4-b]pyridine is a privileged scaffold found in many small drug molecules that possess a wide range of pharmacological properties. Efforts to further develop and exploit synthetic methodologies that permit the functionalization of this heterocyclic moiety warrant investigation. To this end, a series of novel 1,3-disubstituted pyrazolo[3,4-b]pyridine-3-carboxamide derivatives have been prepared by introducing the 3-carboxamide moiety using palladium-catalyzed aminocarbonylation methodology and employing CO gas generated ex situ using a two-chamber reactor (COware®). The functional group tolerance of this optimized aminocarbonylation protocol is highlighted through the synthesis of a range of diversely substituted C-3 carboxamide pyrazolo[3,4-b]pyridines in excellent yields of up to 99%.
Keywords: pyrazolo[3,4-b]pyridine; 7-azaindazole; palladium; aminocarbonylation; carboxamide